THE PORTRAYAL OF RACIAL DIDSCRIMINATION TOWARDS THE CHARACTERS IN MY NAME IS LEON NOVEL BY KIT DE WAAL - Selvira Setia Avisa; M. Natsir; Fatimah M. (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2022)
ABSTRACT The study aims to discover the types of racial discrimination portrayed in Kit De Waal’s My Name is Leon novel as well as to identify the discrimination seen through the colored characters in the novel. The researcher uses the qualitative research with a mimetic approach to conduct the research. The data source of the study is Kit De Waal’s My Name is Leon novel. The data are collected from the narration and dialogues related to the racial discrimination toward the characters through the characterization depicted by the characters. The theories that are used in this study are Blank’s theory of Measuring Racial Discrimination and Kenan’s theory of narration. The results of this study show that explicit and intentional discrimination (verbal antagonism, avoidance, segregation, and physical attack), subtle prejudice, and organizational process are portrayed in this novel seen through the characters’ direct and indirect presentation which involve their characterization such as their speeches, actions, external appearances, and the environments related to the racial discrimination issue depicted in the story.Keywords: My Name is Leon, Discrimination, Racism, Indirect Presentation ABSTRAK Penelitian ini bertujuan untuk menemukan jenis-jenis diskriminasi rasial yang digambarkan dalam novel Kit De Waal berjudul My Name is Leon serta untuk mengidentifikasi diskriminasi yang dilihat melalui tokoh-tokoh di dalam novel. Penelitian ini merupakan penelitian kualitatif yang menggunakan pendekatan mimesis. Sumber data dari penelitian ini adalah novel karya Kit De Waal berjudul My Name is Leon. Data tersebut dikumpulkan dari narasi dan dialog yang terkait dengan diskriminasi rasial terhadap tokoh-tokoh melalui karakterisasi yang digambarkan oleh para tokoh. Teori-teori yang digunakan untuk penelitian ini adalah Teori Pengukuran Diskriminasi Rasial dari Blank dan teori Kenan mengenai teori narasi. Hasil penelitian ini menunjukkan bahwa diskriminasi eksplisit dan disengaja (antagonisme verbal, penghindaran, segregasi, dan serangan fisik), prasangka licik dan proses organisasi digambarkan dalam novel ini dilihat melalui presentasi tidak langsung dari karakter berkulit hitam yang melibatkan karakterisasi mereka seperti wicara, tingkah laku, penampilan luar, dan lingkungan yang terkait dengan isu diskriminasi rasial yang tergambarkan dalam cerita tersebut.Kata Kunci: My Name is Leon, Diskriminasi, Rasisme, Presentasi Tidak Langsung